EVALUATION OF CONTRAST SENSITIVITY IN DETECTING SUBCLINICAL OPTIC NEUROPATHY FOLLOWING ETHAMBUTOL THERAPY - Dr. Sarbori Saha; Dr. Diki Ongmu Shenga (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Ethambutol, widely used in the treatment of tuberculosis, is associated with the risk of optic neuropathy, potentially leading to irreversible vision loss if not detected early. Subclinical optic toxic neuropathy, characterized by early changes in optic function without overt symptoms, can be challenging to diagnose using standard ophthalmic tests. Contrast sensitivity measurement has emerged as a sensitive tool for detecting these early changes. This study aims to evaluate the effectiveness of contrast sensitivity testing in identifying subclinical optic neuropathy in patients undergoing ethambutol therapy, providing critical insights into early intervention and management